IMPROVEMENT OF PRACTICAL TRAINING IN MEDICAL STUDENTS LEARNING THE BASICS OF INTERNAL MEDICINE - Баланюк, Ирина; Поддубная, Антонина; Крупчук, Марина; Шпак, Богдана; Гончарук, Людмила (SWorldJournal, 2022)
The article presents data on value, forms and methods of formation of practical skills in medical students. The above study of methods and tools, which are used in presenting the discipline "Basics of Internal Medicine" for students of medical and pediat